Physical and Covalent Immobilization of Lipase onto Amine Groups Bearing Thiol-Ene Photocured Coatings - ÇAKMAKÇI, EMRAH; DEMİR, SERAP (HUMANA PRESS INC, 2017)
In this study, amine groups containing thiol-ene photocurable coating material for lipase immobilization were prepared. Lipase (EC 3.1.1.3) from Candida rugosa was immobilized onto the photocured coatings by physical adsorption and glutaraldehyde-activated covalent bonding methods, respectively. The catalytic efficiency of the immobilized and free enzymes was determined for the hydrolysis of p-nitrophenyl palmitate and also for the synthesis of p-nitrophenyl linoleate. The storage stability and the reusability of the immobilized enzyme and the effect of temperature and pH on the catalytic activities were also investigated. The optimum pH for free lipase and physically immobilized lipase was determined as 7.0, while it was found as 7.5 for the covalent immobilization. After immobilization, the optimum temperature increased from 37 A degrees C (free lipase) to 50-55 A degrees C. In the end of 15 repeated cycles, covalently bounded enzyme retained 60 and 70 % of its initial activities for hydrolytic and synthetic assays, respectively. While the physically bounded enzyme retained only 56 % of its hydrolytic activity and 67 % of its synthetic activity in the same cycle period. In the case of hydrolysis V (max) values slightly decreased after immobilization. For synthetic assay, the V (max) value for the covalently immobilized lipase was found as same as free lipase while it decreased dramatically for the physically immobilized lipase. Physically immobilized enzyme was found to be superior over covalent bonding in terms of enzyme loading capacity and optimum temperature and exhibited comparable re-use values and storage stability. Thus, a fast, easy, and less laborious method for lipase immobilization was developed.
Keywords: Lipase; Thiol-ene; Covalent immobilization; Physical adsorption; Photocuring; CANDIDA-RUGOSA LIPASE; ALPHA-AMYLASE; ENZYME IMMOBILIZATION; CHEMICAL-MODIFICATION; CROSS-LINKING; GLUTARALDEHYDE; STABILITY; MEMBRANE; SUPPORTS; PURIFICATION